(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The aim of the work was to evaluate the effect of the acidic treatment temperature of aspen sawdust as a filler on the moisture sorption, wetting and mechanical properties of wood-polymer composites. Aspen wood sawdust was treated with the dilute hydrochloric acid solution at 60oC and 90oC during 5 h. Both the treated particles and the filled composites were studied in terms of moisture sorption and wettability; their surface free energy was calculated using the Owens-Wendt-Rabel-Kaelble (OWRK) approach. The obtained results have shown that the acidic treatment of aspen wood sawdust at 90oC leads to an increase in its hydrophobicity that decreases the wettability and moisture sorption of the obtained composite and increases its mechanical properties.